2022
DOI: 10.1039/d2cy01102f
|View full text |Cite
|
Sign up to set email alerts
|

Atomically dispersed Ag on δ-MnO2viacation vacancy trapping for toluene catalytic oxidation

Abstract: The regulation of metal-support interaction (MSI) and the improvement of noble metal utilization are the frontiers of volatile organic compounds (VOCs) catalytic oxidation. Here, we report a H2O2-assisted synthesis process...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…For all MnO x /ZrO 2 catalysts, the binding energies of Mn 2p located at 641.0, 642.5, and 643.5 eV were distinguished, which could be assigned to Mn 2+ , Mn 3+ , and Mn 4+ , respectively. 29–32 Their concentrations for the fresh sample were 44.9%, 16.4%, and 38.7%, respectively. After reduction by plasma, the contents of Mn 3+ and Mn 4+ decreased to 14.5% and 35.4%, respectively, and that of Mn 2+ increased to 50.1% accordingly.…”
Section: Resultsmentioning
confidence: 96%
“…For all MnO x /ZrO 2 catalysts, the binding energies of Mn 2p located at 641.0, 642.5, and 643.5 eV were distinguished, which could be assigned to Mn 2+ , Mn 3+ , and Mn 4+ , respectively. 29–32 Their concentrations for the fresh sample were 44.9%, 16.4%, and 38.7%, respectively. After reduction by plasma, the contents of Mn 3+ and Mn 4+ decreased to 14.5% and 35.4%, respectively, and that of Mn 2+ increased to 50.1% accordingly.…”
Section: Resultsmentioning
confidence: 96%
“…Wang et al 32 reported the synthesis of nanorod-like α-MnO 2 with 3-, 4-, and 5-coordinated Mn exposed on the surface via a hydrothermal method. Yang et al 33 proposed a novel surface treatment technique involving H 2 O 2 -assisted etching and Mn leaching through the H 2 O 2 –MnO 2 redox reaction. This method enables the artificial creation of Mn vacancies on surfaces.…”
Section: New Strategies For the Construction Of Mnox-based Heterogene...mentioning
confidence: 99%
“…(g) Toluene conversion with different catalysts. Reproduced with permission from ref . Copyright 2022, Royal Society of Chemistry.…”
Section: Mo-confined Adcs For the Removal Of Individual Flue Gas Poll...mentioning
confidence: 99%
“…Moreover, Hu et al 90 pointed out that the Ag 1 in Ag 1 /HMO presented a higher electronic density of states (Figure 5c), which would interact strongly with O atoms through the hybridization of Ag d orbitals with O p orbitals, thus favoring the O 2 activation and the nucleophilicity of surface lattice oxygen. Notably, Yang et al 91 found that the formation of OV on Ag 1 /MnO 2 was significantly promoted by Ag 1 . As shown in Figure 5d, the decrease in peak α of samples indicated the presence of ligand holes around Mn 4+ (3d 3 ), forming Mn 3+ (3d 4 L), i.e., OV.…”
Section: Voc Degradationmentioning
confidence: 99%